ENHANCING STUDENTS’ SPEAKING SKILLS WITH LANGUAGE GAMES - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
The article considers the possibilities of using speaking games in the process of teaching a foreign language at a university. The main classifications of games are given, while the main attention is paid to games of a lexical nature. The article substantiates the conditions that allow the most effective use of speaking games in foreign language classes, and also provides examples of games at different stages of working with students. Examples of games in a foreign language lesson with different stages of work with students are given to enhance students’ speaking skills.